Breaking the athletics world record in the 100 and 400 meters: an alternative method for assessment - Santos, P. A.; Sousa, C. V.; Barbosa, L. P.; Aguiar, S. S.; Sales, M. M.; Simões, H.; Nikolaidis, B. T.; Knechtle, B. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: The top 10 athletes in the International Association of Athletic Federations in 100-m and 400-m ranking for each sex were assessed for their history of race times before achieving their personal record (PR). The main goal of this study was to create a new method for optimal performance improvement rate assessment for coaches and athletes aiming the World Record. METHODS: The difference between PR (`current` season) and the best race time in the last season was defined as the first season improvement rate (1-SIR), whereas the average improvement rate in the last and preceding seasons was the multi-season improvement rate (M-SIR). 1-SIR and M-SIR were calculated for each athlete. RESULTS: The sex comparison for the 100 m event showed a significant difference in the M-SIR in favor of women. No statistical differences were identified for the 400 m event, with a trivial effect in both 1-SIR and M-SIR. CONCLUSIONS: As a practical applicability, graph plots were designed to help verifying the improvement rate of athletes and to evaluate whether a long-term training strategy induced an acceptable performance improvement or whether some adjustments needed and check within the plots if the improvement rate is within the average of the top-10 athletes of their event.